TEACHER'S PERCEPTION OF USING ENGLISH TEXTBOOK IN TEACHING ENGLISH FOR MADRASAH IBTIDAIYAH MUNAWWAROH JAMBI - Heri Gunawan, Muhammad (Langue (Journal of Language and Education), 2023)
This study aimed to investigate teachers’ perceptions toward the use of English textbooks in teaching English and identify the teachers' obstacles to using the textbook. The participants of the study were two English teachers at an Islamic elementary school in Jambi. The study used a descriptive-qualitative approach and data collected through an interview. The results indicated that teachers had a positive attitude toward the textbook. Teachers employed textbook adaptation strategies by modifying tasks and adding and removing materials when using the textbook. Teachers encountered two major challenges: the level of difficulty of the material and limited instructional tools. The study's findings are likely to enhance teachers' knowledge of appropriate textbook criteria and to create meaningful and communicative purposes for future textbooks. Keywords: perception, textbook, Islamic school, adapting material